Enhancing the privacy risk awareness of teenagers in online social networks through soft-paternalism mechanisms. Issue 129 (September 2019) - Alemany, J.; del Val, E.; Alberola, J.; García-Fornes, A.
Highlights: Two mechanisms to educate users about the privacy risk of publishing information. Picture Nudge and Number Nudge are based on soft-paternalism mechanisms. Both mechanisms use the metric of privacy, PRS, to assess the risks of publishing. We did an experiment with 42 teenagers to test the effects of mechanisms. The results confirm that the proposed mechanisms can be considered a useful tool for enhancing privacy awareness in social networks. Abstract: Privacy Risk in Online Social Networks (OSNs) is one of the main concerns that has increased in the last few years. Even though social network applications provide mechanisms to control risk, teenagers are not often aware of the privacy risks of disclosing information in online social networks. The privacy decision-making process is complex and users often do not have full knowledge and enough time to evaluate all potential scenarios. They do not consider the audience that will have access to disclosed information or the risk if the information continues to spread and reaches an unexpected audience. To deal with these issues, we propose two soft-paternalism mechanisms that provide information to the user about the privacy risk of publishing information on a social network. That privacy risk is based on a complex privacy metric. To evaluate the mechanisms, we performed an experiment with 42 teenagers. The proposed mechanisms were included in a social network calledPesedia . The results show that there are significant differences in teenagers' behaviors towards better privacy practices when the mechanisms are included in the network.